2017
DOI: 10.1016/j.sjbs.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Gene introgression from common wheat into Aegilops L.

Abstract: Group of experiments were carried out to verify possibility of gene introgression from common wheat into . The artificial indoor crossbreed was conducted using 7 genotypes from 4 wheat relative species as female, and common wheat as male. The experiment result shows that different species has variable cross ability. Among the 4 Aegilops species, the highest cross rate is from the combination of × (46.49% for genotype Ae42, 22.58% for Y92), the second is from × (14.76% for Y100, 12.11% for Ae23), the third is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The seed-setting rate with Aegilops as female parents is variable across these species. Yuan et al (2017) reported the rate was about 0.2% in Ae. speltoides × bread wheat, 2–9% in Ae.…”
Section: Hybridization Barriers Between Wheat and Aegilops Species Anmentioning
confidence: 97%
See 1 more Smart Citation
“…The seed-setting rate with Aegilops as female parents is variable across these species. Yuan et al (2017) reported the rate was about 0.2% in Ae. speltoides × bread wheat, 2–9% in Ae.…”
Section: Hybridization Barriers Between Wheat and Aegilops Species Anmentioning
confidence: 97%
“…tauschii × bread wheat crosses. Even though the initial seed-setting rate was a 47% (Yuan et al, 2017), the seedling formation rate dropped to 1%. Sehgal et al (2011) reported that an average of 35% initial embryo formation ended in an average of 7% F 1 plants.…”
Section: Endosperm and Embryo Development Deficiency And Embryo Rescuementioning
confidence: 99%
“…Sequencing, expression studies, functional annotations, and high-throughput genomics analysis can accelerate allele mining for several traits in sets of chromosome segment substitution lines. Though genetic diversity in wild wheat is a useful resource for trait discovery, only limited numbers of wild relatives have been exploited due to the weedy morphology and low fertility of interspecific hybrids [17]. To utilize the genes and alleles conferring abiotic and biotic stress tolerance from wild relatives of wheat, different genetic materials in the form of addition, substitution, and translocation lines have been developed after laborious efforts in the last few decades [18].…”
Section: Introductionmentioning
confidence: 99%
“…ventricosa. Yuan, et al 47 reported the production of Ae. cylindrica × T. aestivum hybrids that showed 0 to less that 1% seed set in back-crosses.…”
Section: Discussionmentioning
confidence: 99%